2020
DOI: 10.3892/ol.2020.12197
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular heterogeneity of guanine nucleotide binding‑protein γ subunit 4 in left‑ and right‑sided colon cancer

Abstract: Molecular heterogeneity determines the differences in the pathological features, prognosis and survival after relapse when comparing left-sided colon cancer (LCC) and right-sided colon cancer (RCC). At present, the discrepancy in the underlying molecular events between the two types of colon cancer has not been thoroughly investigated. The present study aimed to explore novel targets to predict the disease stage and prognosis of LCC and RCC. Expression analysis of guanine nucleotide binding-protein γ subunit 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…These results suggest that GNG4 expression is a prognostic biomarker of OS. Although many studies have suggested that GNG4 may be a biomarker for poor prognosis in a variety of tumours (19)(20)(21)(22)(23)(24), this study is the first to investigate the correlation between GNG4 expression and prognosis in OS. Considering that metastasis and GNG4 are strong prognostic factors for OS, a nomogram was constructed that combined metastasis and GNG4 expression with clinical data.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These results suggest that GNG4 expression is a prognostic biomarker of OS. Although many studies have suggested that GNG4 may be a biomarker for poor prognosis in a variety of tumours (19)(20)(21)(22)(23)(24), this study is the first to investigate the correlation between GNG4 expression and prognosis in OS. Considering that metastasis and GNG4 are strong prognostic factors for OS, a nomogram was constructed that combined metastasis and GNG4 expression with clinical data.…”
Section: Discussionmentioning
confidence: 95%
“…Many previous studies have shown that GNG4 may be a diagnostic marker for various cancers, and GNG4 is highly expressed in different types of cancers, including rectal, colon, stomach, lung adenocarcinoma, and gallbladder cancers (19)(20)(21)(22)(23)(24). In the TCGA data, our analysis also confirmed that GNG4 was significantly overexpressed in OS and most other tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected to be a targeted drug for the treatment of diabetes and obesity ( Kanematsu-Yamaki et al, 2017 ). Upregulation of G-protein subunit γ4 ( GNG4 ) is associated with many cancers, such as colon cancer ( Song et al, 2020 ), triple-negative breast cancer ( Zhang et al, 2020 ), thymic carcinoma ( Kishibuchi et al, 2020 ), and hepatocellular carcinoma ( Ding et al, 2019 ). It was found that G-protein γ7 ( GNG7 ) is a tumor suppressor gene in the progression of renal cell carcinoma (RCC) and is a novel replacement gene in the treatment of RCC ( Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%